Electrolyte additive containing silicon group, amide group and fluorine atom, metal lithium battery electrolyte and metal lithium battery
By using electrolyte additives containing silicon, amide, and fluorine atoms in metal lithium batteries, a high mechanical strength SEI film and an ultra-thin CEI film are formed in metal lithium batteries, which solves the problems of insufficient mechanical strength of the SEI film under high potential and high temperature conditions and the reaction of LiPF6 with trace water to form HF, which significantly improves the cycle stability and safety of the battery.
Patent Information
- Application Number
- CN202510061731.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-04
Smart Images

Figure CN119764573A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to an electrolyte additive containing silicon groups, amide groups and fluorine atoms, a metal lithium battery electrolyte and a metal lithium battery. Background Art
[0002] With the rapid development of portable electronic products and new energy vehicles, the demand for high energy density batteries is becoming increasingly urgent to meet the development trend of miniaturization and thinness. The theoretical specific capacity of traditional graphite anode is only 372 mAhg -1 , which limits the energy density of lithium-ion batteries with graphite as the negative electrode. The metallic lithium negative electrode (Li) has the highest theoretical specific capacity (3860mAhg -1 ) and the most negative electrode potential (-3.04Vvs standard hydrogen electrode), it is considered to be the most ideal negative electrode material. However, the continuous growth of lithium dendrites, the huge volume change during lithium deposition / stripping, and the unstable solid electrolyte interface film cause the capacity decay and poor cycle stability of metal lithium batteries, and even cause serious safety problems such as battery short circuit.
[0003] In response to the problems of metallic lithium negative electrodes, researchers have mainly modified metallic lithium from the aspects of electrolyte additives, non-in-situ interface film construction, and composite three-dimensional skeleton materials. Among them, electrolyte additives have obvious advantages over other modification methods. They do not need to change any structure of the battery, are simple to operate, easy to industrialize, and have high economic feasibility. However, the electrolyte additive modification schemes reported so far still face problems such as insufficient mechanical strength of the formed SEI film and high battery impedance. In addition, under high potential and high temperature conditions, the LiPF in the electrolyte 6 It will react with trace water in the electrolyte system to generate HF, which will accelerate the dissolution of metals on the surface of high-nickel ternary materials, nickel-manganese-lithium oxide, etc. It will not only corrode the positive and negative electrode surfaces and destroy the electrode structure, but also accelerate the decomposition of the electrolyte, eventually causing battery failure. Therefore, how to develop a new electrolyte additive that can be derived on the surface of metal lithium with high ion diffusion capacity, high Young's modulus SEI film, and can effectively remove water and reduce acid is an important technical problem that needs to be solved urgently. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides an electrolyte additive containing silicon groups, amide groups, and fluorine atoms, a metal lithium battery electrolyte, and a metal lithium battery, and the technical scheme thereof is as follows: An electrolyte additive containing silicon groups, amide groups, and fluorine atoms is 2,2,2-trifluoro-N,N-bis(trimethylsilyl)acetamide, and its structural formula is as follows: .
[0005] A metal lithium battery electrolyte contains the above-mentioned electrolyte additive containing silicon groups, amide groups and fluorine atoms.
[0006] Furthermore, the preparation method of the metal lithium battery electrolyte is as follows: first, in the temperature range of 35 to 45° C., a non-aqueous organic solvent and a lithium salt are mixed evenly to obtain a basic electrolyte for a metal lithium battery; then, an electrolyte additive containing a silicon group, an amide group, or a fluorine atom is added to the basic electrolyte, and the mixture is mixed evenly to obtain a metal lithium battery electrolyte.
[0007] Furthermore, the amount of the electrolyte additive is 0.01wt% to 10wt% of the total mass of the metal lithium battery electrolyte.
[0008] Furthermore, the amount of the electrolyte additive is 0.05wt% to 2wt% of the total mass of the metal lithium battery electrolyte.
[0009] Furthermore, the non-aqueous organic solvent is a carbonate or ether solvent.
[0010] Furthermore, the carbonate solvent is at least one of propylene carbonate, ethylene carbonate, methyl propyl carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, ethyl acetate, methyl acetate, and 1,4-butyl propyl carbonate; the ether solvent is at least one of ethylene glycol dimethyl ether, tetrahydrofuran, 1,2-dimethoxyethane, diethylene glycol dimethyl ether, 1,3-dioxolane, dimethoxymethane, tetraethylene glycol dimethyl ether, ethylene glycol diethyl ether, and diethylene glycol diethyl ether.
[0011] Furthermore, the lithium salt is at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(difluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium (fluorosulfonyl)(perfluorobutylsulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate, and lithium trifluoromethylsulfonate; and the molar concentration of the lithium salt is 0.3 mol / L to 3 mol / L.
[0012] Furthermore, the molar concentration of the lithium salt is 0.8 mol / L to 1.5 mol / L.
[0013] A metal lithium battery comprises an electrolyte and positive and negative electrodes; the electrolyte adopts the metal lithium battery electrolyte described above; the negative electrode is metal lithium, and the positive electrode is at least one of lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide and lithium-rich manganese base.
[0014] Compared with the prior art, the present invention mainly has the following beneficial technical effects: 1. The electrolyte additive containing silicon group, amide group and fluorine atom provided by the present invention is 3The combination of Si-N bonds and amide groups forms a stable electrode / electrolyte interface film on the positive and negative electrode surfaces, which can reduce the surface of the metallic lithium negative electrode to generate high mechanical strength, high stability, and fast Li + The SEI film transmitted by the electrolyte additive of the present invention forms an ultra-thin and stable CEI film on the surface of the positive electrode, which effectively blocks the dissolution-deposition behavior of transition metals on the surface of the positive electrode, and can effectively remove water and reduce acid, inhibiting the corrosion of HF and other substances on the positive electrode. Since the electrolyte additive of the present invention constructs a "multifunctional" interface film at the interface between the positive and negative electrodes at the same time, it effectively improves the electrochemical performance of metal lithium batteries, especially the cycle performance under high temperature and high pressure.
[0015] 2. The electrolyte additive used in the present invention contains an amide functional group, which can form an ultra-thin, uniform, and highly ion-conductive interface film at the interface between the positive and negative electrodes in preference to the solvent, thereby solving the problem of increased interfacial impedance and increased battery polarization formed by general electrolyte additives on the surfaces of the positive and negative electrodes, which leads to reduced capacity.
[0016] 3. The electrolyte additive contains Si-N bonds in its structure, which can spontaneously react with trace water in the electrolyte to generate cyclic products, thus avoiding the reaction of trace water with lithium salts to produce corrosive HF that damages structures such as electrodes and current collectors, and improving the cycle stability of metal lithium batteries, especially the cycle stability under high temperature and high pressure.
[0017] 4. The electrolyte additive contains -CF 3 Through the strong electron-withdrawing effect of fluorine atoms, LiF is formed in situ. LiF has good mechanical strength (shear modulus of 55.1 GPa) and high interfacial energy to metallic lithium (73.28 meVÅ -2 ), which can effectively inhibit the growth of lithium dendrites and improve the coulombic efficiency and cycle performance of metal lithium batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The Li|NCM622 battery 55 prepared in Example 1 and Comparative Example 1 of the present invention o C Cyclic performance comparison curve under high temperature conditions; Figure 2 2 is a comparison curve of the room temperature cycle performance of Li|NCM811 batteries prepared in Example 2 of the present invention and Comparative Example 2; Figure 3 Li|LiMn prepared in Example 3 of the present invention and Comparative Example 3 0.6 Fe 0.4 PO 4 Comparison curve of battery cycle performance. DETAILED DESCRIPTION
[0019] The present invention is further described below in conjunction with specific embodiments and drawings. It should be noted that the following embodiments are merely exemplary and should not be used to limit the scope of protection of the present invention. Example 1
[0020] In a glove box filled with argon, two organic solvents, ethyl methyl carbonate and ethylene carbonate, were mixed evenly in a volume ratio of 1:1, and lithium hexafluorophosphate was added and mixed evenly to prepare a clear and transparent metal lithium battery basic electrolyte, which was marked as sample 1, wherein the concentration of lithium hexafluorophosphate was 1 mol / L; and then 2,2,2-trifluoro-N,N-bis(trimethylsilyl)acetamide additive was added to the basic electrolyte, and the mass fraction of the additive was 0.05wt%.
[0021] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no additive is added to the electrolyte.
[0022] The following electrochemical performance tests were performed on the electrolytes of Example 1 and Comparative Example 1: The electrolyte containing silicon-based, amide-based, and fluorine-based electrolyte additives obtained in Example 1 and the common electrolyte of Comparative Example 1 were used respectively, with metallic lithium as the negative electrode and an area loading of 6 mg cm -2 The NCM622 was used as the positive electrode and assembled into a button cell in an argon atmosphere. o C, it was first activated at a rate of 0.2C for three cycles in the voltage range of 2.8-4.3V, and then cycled at a rate of 1C for a long time. The results are shown in the attached figure. Figure 1 shown.
[0023] Figure 1 The results show that in 55 o After 100 cycles at 1C at high temperature of C, the discharge specific capacity of the Li|NCM622 battery using the electrolyte of Example 1 is 155.5 mAh / g, while the discharge specific capacity of the Li|NCM622 battery using the electrolyte of Comparative Example 1 is 143.6 mAh / g, indicating that the 2,2,2-trifluoro-N,N-bis(trimethylsilyl)acetamide additive added in Example 1 is beneficial to improving the high temperature cycle performance of the battery. Example 2
[0024] In a glove box filled with argon, three organic solvents, ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate, were mixed evenly in a volume ratio of 1:1:1, and lithium hexafluorophosphate was added and mixed evenly to prepare a clear and transparent metal lithium battery basic electrolyte, which was marked as sample 2, wherein the concentration of lithium hexafluorophosphate was 1 mol / L; then 2,2,2-trifluoro-N,N-bis(trimethylsilyl)acetamide additive was added to the basic electrolyte, and the mass fraction of the additive was 0.3wt%.
[0025] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that no additive is added to the electrolyte.
[0026] The following electrochemical performance tests were performed on the electrolytes of Example 2 and Comparative Example 2: The electrolyte containing electrolyte additives obtained in Example 2 and the common electrolyte of Comparative Example 2 were respectively used to assemble Li|NCM811 full cells in an argon atmosphere. The full cells were first activated at a rate of 0.2C for three cycles, and then subjected to a long cycle test at a rate of 1C. Figure 2 As shown in the figure, the discharge capacity of the Li|NCM811 full battery in Example 2 in the first 16 cycles is slightly lower than that in the full battery in Comparative Example 2. This may be because the film formation of the additives in the first few cycles consumes part of the capacity. After 300 cycles, the discharge capacity of the full battery in Example 2 is still 167.76 mAh g -1 , the capacity retention rate is 88.1%, while the battery capacity retention rate of comparative example 2 is only 73%. Example 3
[0027] In a glove box filled with argon, three organic solvents, ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate, were mixed evenly in a volume ratio of 1:1:1, and lithium hexafluorophosphate was added and mixed evenly to prepare a clear and transparent basic electrolyte, which was marked as sample 3, wherein the concentration of lithium hexafluorophosphate was 1 mol / L; and then 2,2,2-trifluoro-N,N-bis(trimethylsilyl)acetamide additive was added to the basic electrolyte, and the mass fraction of the additive was 0.1wt%.
[0028] Comparative Example 3 The difference between Comparative Example 3 and Example 3 is that no additive is added to the electrolyte.
[0029] The following electrochemical performance tests were performed on the electrolytes of Example 3 and Comparative Example 3: The electrolyte containing the electrolyte additive obtained in Example 3 and the ordinary electrolyte of Comparative Example 3 were respectively used to assemble Li|LiMn 0.6 Fe 0.4 PO 4 Full battery. The full battery was first activated at a rate of 0.2C for three cycles, and then tested at a rate of 1C for a long cycle. Figure 3 As shown, the Li|LiMn electrolyte of Example 3 is used 0.6 Fe 0.4 PO 4 After 100 cycles at 1C rate, the discharge capacity is 117.9 mAh / g, while the Li|LiMn 0.6Fe 0.4 PO 4 The battery's discharge specific capacity is only 103.6mAh / g. Example 4
[0030] In a glove box filled with argon, three organic solvents, ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate, are mixed evenly in a volume ratio of 1:1:1, and lithium hexafluorophosphate is added and mixed evenly to prepare a clear and transparent basic electrolyte, wherein the concentration of lithium hexafluorophosphate is 1 mol / L; then different mass fractions of 2,2,2-trifluoro-N,N-bis(trimethylsilyl)acetamide additive are added to the basic electrolyte to prepare electrolytes containing different mass fractions of additives.
[0031] Comparative Example 4 The difference between Comparative Example 4 and Example 4 is that no additive is added to the electrolyte.
[0032] The following electrochemical performance tests were performed on the electrolytes of Example 4 and Comparative Example 4: A series of electrolytes containing different mass fractions of additives obtained in Example 4 and the common electrolyte of Comparative Example 4 were respectively used to assemble Li|NCM811 full batteries in an argon atmosphere. o Under high temperature conditions of 1.37°C, the full battery was first activated at a rate of 0.2C for three cycles, and then subjected to a long cycle test at a rate of 1C for 100 times.
[0033] The results of high temperature cycle tests of Li|NCM811 full batteries containing electrolytes with different mass fractions of additives are shown in Appendix 1.
[0034] Table 1 High temperature cycle test of full battery containing electrolytes with different mass fractions of additives ; As can be seen from Table 1, when the mass fraction of the additive is 0.15wt%, the high-temperature cycle test has the best effect. The discharge capacity at the 100th cycle reaches 166.8, which is 17.6 higher than that without additives. The capacity retention rate after 100 times reaches 86.6%, which is 13.8% higher than that without additives. Example 5
[0035] In a glove box filled with argon, two organic solvents, ethylene glycol dimethyl ether and 1,3-dioxolane, were mixed evenly in a volume ratio of 1:1, and lithium bis(trifluoromethylsulfonyl)imide was added and mixed evenly to prepare a clear and transparent metal lithium battery basic electrolyte, wherein the concentration of lithium bis(trifluoromethylsulfonyl)imide was 1 mol / L; and then 2,2,2-trifluoro-N,N-bis(trimethylsilyl)acetamide additive was added to the basic electrolyte, and the mass fraction of the additive was 0.1 wt%.
[0036] Comparative Example 5 The difference between Comparative Example 5 and Example 5 is that no additive is added to the electrolyte in this comparative example.
[0037] The following electrochemical performance tests were performed on the electrolytes of Example 5 and Comparative Example 5: The electrolyte of Example 5 and the common electrolyte of Comparative Example 5 were used respectively, and the positive and negative electrodes of the battery were both made of metallic lithium to assemble into a Li|Li symmetrical battery. The battery was tested at 2 mA cm -2 、2mAhcm -2 Cycling performance under the following conditions. The polarization potential of the lithium symmetric battery of comparative example 5 without additives increased rapidly after cycling for 168 hours, while the lithium symmetric battery using the electrolyte of example 5 maintained a stable lithium deposition / dissolution curve during the 300-hour cycle, and the polarization potential value was also stable at about 28 mV. Example 6
[0038] In a glove box filled with argon, two organic solvents, ethylene glycol dimethyl ether and 1,3-dioxolane, were mixed evenly in a volume ratio of 1:1, and lithium bis(trifluoromethylsulfonyl)imide with a concentration of 1 mol / L was added and mixed evenly to prepare a clear and transparent metal lithium battery basic electrolyte; then 2,2,2-trifluoro-N,N-bis(trimethylsilyl)acetamide additive was added to the basic electrolyte, and the mass fraction of the additive was 0.15 wt%.
[0039] Comparative Example 6 The difference between Comparative Example 6 and Example 6 is that no additive is added to the electrolyte.
[0040] The following electrochemical performance tests were performed on the electrolytes of Example 6 and Comparative Example 6: The metal lithium battery electrolyte containing electrolyte additives obtained in Example 6 and the common electrolyte of Comparative Example 6 were respectively used to assemble a lithium-sulfur full battery in an argon atmosphere, and the positive electrode sulfur loading was 8 mg cm -2 , and long cycles were performed at a rate of 0.5C. When the lithium-sulfur full battery using the electrolyte of comparative example 6 without additives was cycled to the 78th cycle, a short circuit occurred in the battery due to lithium dendrites piercing the diaphragm, while the lithium-sulfur battery using the electrolyte of example 6 could be cycled stably for 100 cycles without short circuit in the battery, and there was still 5.3 mAh cm after 100 cycles. -2 The specific capacity is about . Example 7
[0041] In a glove box filled with argon, two organic solvents, ethyl methyl carbonate and ethylene carbonate, were mixed evenly in a volume ratio of 1:1, and lithium hexafluorophosphate was added and mixed evenly to prepare a basic electrolyte with a lithium hexafluorophosphate concentration of 1 mol / L; then 2,2,2-trifluoro-N,N-bis(trimethylsilyl)acetamide additive was added to the basic electrolyte, and the mass fraction of the additive was 0.2wt%.
[0042] Comparative Example 7 The difference between Comparative Example 7 and Example 7 is that no additive is added to the electrolyte.
[0043] The following electrochemical performance tests were performed on the electrolytes of Example 7 and Comparative Example 7: The electrolytes in Example 7 and Comparative Example 7 were respectively used, with metallic lithium as the negative electrode and LiNi 0.5 Mn 1.5 O 4 As the positive electrode, the button cell was assembled in an argon atmosphere. o C, activated three times at a rate of 0.2C, and then cycled 100 times at a rate of 1C. After 100 cycles, the electrolyte of Example 7 was added. 0.5 Mn 1.5 O 4 The battery capacity retention rate is 91.8%, while the Li|LiNi 0.5 Mn 1.5 O 4 The battery capacity retention rate is only 84.6%.
Claims
1. An electrolyte additive containing silicon groups, amide groups, and fluorine atoms, characterized in that: The electrolyte additive is 2,2,2-trifluoro-N,N-bis(trimethylsilyl)acetamide, and its structural formula is as follows: 。 2. A metal lithium battery electrolyte, characterized in that: The metal lithium battery electrolyte contains the electrolyte additive containing silicon groups, amide groups and fluorine atoms as described in claim 1.
3. A metal lithium battery electrolyte according to claim 2, characterized in that: The preparation method of the metal lithium battery electrolyte is as follows: first, in the temperature range of 35 to 45° C., a non-aqueous organic solvent and a lithium salt are mixed evenly to obtain a basic electrolyte for the metal lithium battery; then, an electrolyte additive containing a silicon group, an amide group, and a fluorine atom is added to the basic electrolyte, and the mixture is mixed evenly to obtain the metal lithium battery electrolyte.
4. A metal lithium battery electrolyte according to claim 3, characterized in that: The amount of the electrolyte additive is 0.01wt% to 10wt% of the total mass of the metal lithium battery electrolyte.
5. A metal lithium battery electrolyte according to claim 4, characterized in that: The amount of the electrolyte additive is 0.05wt% to 2wt% of the total mass of the metal lithium battery electrolyte.
6. A metal lithium battery electrolyte according to claim 3, characterized in that: The non-aqueous organic solvent is a carbonate or ether solvent.
7. A metal lithium battery electrolyte according to claim 6, characterized in that: The carbonate solvent is at least one of propylene carbonate, ethylene carbonate, methyl propyl carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, ethyl acetate, methyl acetate, and 1,4-butyl propyl carbonate; the ether solvent is at least one of ethylene glycol dimethyl ether, tetrahydrofuran, 1,2-dimethoxyethane, diethylene glycol dimethyl ether, 1,3-dioxolane, dimethoxymethane, tetraethylene glycol dimethyl ether, ethylene glycol diethyl ether, and diethylene glycol diethyl ether.
8. A metal lithium battery electrolyte according to claim 3, characterized in that: The lithium salt is at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(difluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium (fluorosulfonyl)(perfluorobutylsulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate, and lithium trifluoromethylsulfonate; and the molar concentration of the lithium salt is 0.3 mol / L to 3 mol / L.
9. A metal lithium battery electrolyte according to claim 8, characterized in that: The molar concentration of the lithium salt is 0.8 mol / L to 1.5 mol / L.
10. A metal lithium battery, comprising an electrolyte and positive and negative electrodes, characterized in that: The electrolyte adopts a metal lithium battery electrolyte as described in any one of claims 2-9; the negative electrode is metal lithium, and the positive electrode is at least one of lithium cobalt oxide, lithium iron phosphate, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide and lithium-rich manganese base.
Citation Information
Cited By
Wide-temperature-range semi-solid electrolyte as well as preparation method and application thereof
CN120473562A